2008
DOI: 10.1093/cvr/cvn339
|View full text |Cite
|
Sign up to set email alerts
|

A transient outward potassium current activator recapitulates the electrocardiographic manifestations of Brugada syndrome

Abstract: Aim Transient outward potassium current (Ito) is thought to be central to the activator has not been pathogenesis of the Brugada syndrome (BrS). However, an Ito available with which to validate this hypothesis. Here we provide a direct test of the hypothesis using a novel Ito activator, NS5806. Methods Isolated canine ventricular myocytes and coronary-perfused wedge preparations were used. Results Whole-cell patch-clamp studies showed that NS5806 (10 μM) increased peak Ito at +40 mV by 79±4% (24.5±2.2 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
134
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(143 citation statements)
references
References 28 publications
7
134
2
Order By: Relevance
“…This drug was shown to reverse the effect of induced heart failure in canine models (17,19). On the other hand, Witzel et al (11) hypothesized that the observed current inhibition in hippocampal neuronal cells was likely due to a higher concentration of NS5806 used (20 M) compared with the concentration used in canine cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This drug was shown to reverse the effect of induced heart failure in canine models (17,19). On the other hand, Witzel et al (11) hypothesized that the observed current inhibition in hippocampal neuronal cells was likely due to a higher concentration of NS5806 used (20 M) compared with the concentration used in canine cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of Kv4-KChIP complex has been shown to be necessary for proper regulation of the fast component of the I TO currents in the heart (4) and I SA in the brain (10). Demod-* This work was supported, in whole or in part, by National Institutes of Health ulation of I TO currents is a characteristic trait in hypertrophied and failing hearts (16) as well as in Brugada syndrome (17). Normal functioning heart tissue displays an increasing I TO current density gradient from endocardium to epicardium, which has been shown to correlate with a transmural KChIP density (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported that intravenous administration of quinidine increased RV MAPD 90 at the shortest diastolic interval and decreased the maximum slope of the RV action potential duration restitution curve. 33) Thus, we hypothesized that shorter RA MAPD 80 and a steeper restitution curve at the shorter diastolic interval in Brugada syndrome might also be related to the smaller late sodium current 2) or greater transient outward current 34) at the shorter diastolic interval in Brugada patients. The inducibility of reentrant arrhythmias to a large extent is dependent on the wavelength (conduction velocity × refractory period) of the atrial impulse.…”
Section: )mentioning
confidence: 98%
“…Single myocytes were enzymatically dissociated from the left ventricle as previously described 23 and allowed to settle and attach to the polylysine-coated floor of a 0.5 mL chamber mounted on a stage heater (Model PDMI-2, Harvard Apparatus, Holliston, MA, USA) on a Nikon Eclipse microscope. This chamber was perfused with Tyrode's solution at a rate of 2-3 mL/min prior to and during gigaseal formation.…”
Section: Voltage-clamp Studies Using Canine Epicardial Cellsmentioning
confidence: 99%